Експериментальне визначення параметрів трифазного струмопідводу установок електродугового нагріву - Марущак, Ярослав Юрійович; Кравець, Ігор Петрович; Мусихіна, Наталія Павлівна (НТУ "ХПІ", 2010)
The technique of experimental determination of short network parameters of electric arc furnaces is proposed. The expressions to calculate the values of their own and mutual inductance as well as flexible current conductor resistance based on measurements in a series of two-phase and three-phase short circuit tests are obtained. The usage of these parameters to determine the arc voltage in phases increases accuracy of stabilizing the length and the power of arcs.
Experimental determination of three-phase current conductor parameters for arc heating installations
Keywords: піч електродугова; система автоматичного керування; трансформатор; піч сталеплавильна; електрод